A Descriptive Study to Assess the Knowledge Regarding Breast Cancer Among Nursing Students at Selected Hospitals in Vrindavan, Mathura - Mathew, Blessy (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
Cancer in breast begins when healthy cells in the breast change and grow out of control, forming a mass or sheet of cells called a tumour. A tumour can be cancerous or benign. A cancerous tumour is malignant, meaning it can grow and spread to other parts of the body. A benign tumour means the tumour can grow but will not spread. Breast cancer is the most common, prevalent and diagnosed that affects women and the leading cause of death and disability worldwide and is a leading cause of morbidity and mortality among women.  Breast cancer spreads when the cancer grows into adjacent organs or other parts of the body or when breast cancer cells move to other parts of the body through the blood vessels and/or lymph vessels which is called a metastasis. Objective: To assess the levels of knowledge among nursing students regarding breast cancer at Selected hospital of Vrindavan, Mathura and to find out the relationship   between socio- demographic characteristic and levels of knowledge. Materials and methods: This study was conducted to assess knowledge regarding  Breast Cancer in selected Nursing school in Vrindavan, Mathura and descriptive study design was selected. Population was GNM students and sample size were 80.  Students were selected with convenient sampling technique. Data was collected by using Structured Knowledge Questionnaire. A significant association was found between knowledge score age, religion, and type of family but no association with previous education, area of living, year of study. Operational definitions Knowledge: It refers to the ability of nursing students to respond to questions dealing with breast self-examination as evident knowledge score measured by a structured knowledge Questionnaire Breast self-examination (BSE): It refers to regular systematic examination of both breast and unclear area by women visually and by palpation using her own hand on her breast for the purpose of detecting any abnormality and to report. Nursing students: It refers GNM female students of selected nursing school, Vrindavan, Mathura.
Keywords: Knowledge: Breast self-examination (BSE): Nursing students